Comparative analysis on power quality improvement in autonomous micro grids using PSO, HHO and hybrid controller - Mohammad, Karimulla Syed; Kumar, Ch. Ravi (Institute of Advanced Engineering and Science, 2023)
RES based DG’s are effectively used in DS due to government initiations and benefits. These are also support customer power demands in DS. However, few problems are facing in operation DG’s with existing DS, like parallel operation, islanding detection and majorly power quality problems due go harmonics. In this paper a hybrid control technique proposed to improve the power quality and conversion efficiency. A test case of single phase 3.5 kW PV system based autonomous micro grid is considered. PSO and HHO optimal control strategies are implemented under standard test case and variable test cases. In all the cases Vmpv (V), Impv (A), Vrms (V), Irms (A), Ppv (W), Pg (W), Efficiency (%), THD (%), Inverter Losses (%) are evaluated. In all the cases HHO optimal control strategy for autonomous microgrid exhibits the best performance in comparison with PSO optimal control strategy. The inverter efficiency is improved, inverter losses are reduced and the THD is improved.